Reduced susceptibility to the sound-induced flash fusion illusion in schizophrenia. (30th November 2016) - Vanes, Lucy D.; White, Thomas P.; Wigton, Rebekah L.; Joyce, Dan; Collier, Tracy; Shergill, Sukhi S.
Abstract: Schizophrenia is characterised by the presence of abnormal complex sensory perceptual experiences. Such experiences could arise as a consequence of dysfunctional multisensory integration. We used the sound-induced flash illusion paradigm, which probes audiovisual integration using elementary visual and auditory cues, in a sample of individuals with schizophrenia (n=40) and matched controls (n=22). Signal detection theory analyses were performed to characterise patients' and controls' sensitivity in distinguishing 1 and 2 flashes under varying auditory conditions. Both groups experienced significant fission illusions (whereby one visual flash, accompanied by two auditory beeps, is misperceived as two flashes) and fusion illusions (whereby two flashes, accompanied by one beep, are perceived as one flash). Patients showed significantly lower fusion illusion rates compared to HC, while the fission illusion occurred similarly frequently in both groups. However, using an SDT approach, we compared illusion conditions with unimodal visual conditions, and found that illusory visual perception was overall more strongly influenced by auditory input in HC compared to patients for both illusions. This suggests that multisensory integration may be impaired on a low perceptual level in SZ. Highlights: Patients with schizophrenia are less sensitive to the sound-induced flash fusion illusion This is not accounted for by a more general perceptual bias or visual temporal resolution Reduced capacity for multisensory integration in schizophrenia is evident on an elementary perceptual level